Professional Competence of Arabic Teachers in Education Management - Barokah, Anisatul; Makruf, Imam; Sukardi, Imam (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
The goal of this study is to find out how teacher competency in education management, teacher professional skills, and learning measurement can help make education better. A detailed qualitative method was used for this study. Some of the ways that data is gathered are through interviews, observations, and writing things down. Methods for looking at data, like collecting research materials, making field notes and writing them down, talking to relevant people, using a control trail (data fit test), and triple checking the validity of the data. The results showed that teachers were good at following the directions when planning lessons, making lesson plans, putting together curricula, planning media and learning tools, and planning assessments of learning. The way the teacher teaches is based on mastering the material, structures, concepts, and scientific ways of thinking that support the subjects being taught. The teacher then tests the students' learning based on predetermined learning objectives, which include character tests to see how well they understand concepts, skill tests, and attitude tests about learning. This test is conducted after each subject.